Micro-to macro-scale foraminiferal distributions: the contributions of Martin A. Buzas - Culver, Stephen J (Anuário do Instituto de Geociências, 2006)
The research that Martin A. Buzas has published over the past more than 40 years has influenced us greatly. That research has many strands that cannot be dealt with in this short review. However, the theme of micro- to macroscale foraminiferal distributions is interwoven throughout Buzas's research career. Distributions are something that Buzas is very fond of. He was trained in statistics as well as foraminifera and so it was inevitable that he would combine his knowledge of statistical distributions with foraminiferal distributions at several different scales. He has studied the distribution of foraminifera at microscales, horizontally within a 10 cmÂ² area of the sea floor or vertically, cm by cm within a 20 cm core. He has also worked at the mesoscale, quantifying, through the pioneering use of the General Linear Model, the relationship of foraminiferal distributions and environmental variables in space and time. This research led to the hypothesis of pulsating patches. He has worked at the macroscale with S. J. Culver, defining the distribution of benthic foraminiferal provinces, showing that all foraminiferal distributions, particularly around the coasts of North and Central America, belong to the same statistical distribution. Their work has documented the assembly and disassembly of communities and the latitudinal patterns of deep-sea benthic foraminiferal diversity in the Atlantic basin. Most recently, with his coauthor, mathematical statistician L. C. Hayek, Buzas has delved deep into the intricacies of species diversity and solved a 50 year-old supposedly intractable problem of mathematically relating species richness with species evenness. This work led to the introduction of new approaches to understanding community structure and recognizing boundaries between adjacent communities (SHE analysis). Many of us work long hours and publish many papers over our careers but few of us truly influence the fundamentals of our science. Marty Buzas is one micropaleontologist whose work will be of lasting significance.